2021
DOI: 10.1103/physreva.103.042805
|View full text |Cite
|
Sign up to set email alerts
|

Observation of asymmetric line shapes in precision microwave spectroscopy of the positronium 2S132PJ3

Abstract: We report new measurements of the positronium (Ps) 2 3 S1 → 2 3 PJ fine-structure intervals, ν J (J = 0, 1, 2). In the experiments, Ps atoms, optically excited to the radiatively metastable 2 3 S1 level, flew through microwave radiation fields tuned to drive transitions to the short-lived 2 3 PJ levels, which were detected via the time spectrum of subsequent ground-state Ps annihilation radiation. Both the ν 1 and ν 2 line shapes were found to be asymmetric, which, in the absence of a complete line-shape model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 89 publications
2
19
0
Order By: Relevance
“…However, it was found that the measured ν 0 transition interval disagreed with the QED calculation by more than four standard deviations [5]. Moreover, the ν 1 and ν 2 measurements exhibited unexplained asymmetric line shapes [6] which prevented a precise determination of the corresponding intervals.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…However, it was found that the measured ν 0 transition interval disagreed with the QED calculation by more than four standard deviations [5]. Moreover, the ν 1 and ν 2 measurements exhibited unexplained asymmetric line shapes [6] which prevented a precise determination of the corresponding intervals.…”
Section: Introductionmentioning
confidence: 89%
“…Previously, simulations were performed that were designed to represent the experimental arrangements used in recent measurements of the Ps fine structure [5,6]. However, not all aspects of the experiments were simulated; for example, in the experiments Ps atoms in the 2 3 S 1 level were generated via a single-photon excitation process in a time varying electric field [16].…”
Section: Model Of Experimentsmentioning
confidence: 99%
See 3 more Smart Citations